PENGARUH FINANCIAL DISTRESS, DAN OPINION SHOPPING TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Manik, Cornelius Tona; Taqi, Muhamad; Susanto, Denny (Universitas Muhammadiyah Tangerang, 2024)
A going concern audit opinion is an opinion given or issued by an independent auditor if the company is indicated to have doubts about business continuity (going concern). This research aims to examine the influence of financial distress and opinion shopping on the acceptance of going concern audit opinions with the audit committee as a moderating variable. This research is a type of quantitative research with the data used is secondary data in the form of annual reports of mining companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. The number of samples taken was 23 companies using the purposive sampling method as a sampling technique. The data analysis technique used is logistic regression analysis and Moderated Regression Analysis using the IBM SPSS 25 application. Based on the results of the analysis, it is concluded financial distress and opinion shopping have a negative effect on the acceptance of going concern audit opinions. The result of the role of the moderating variable is that the audit committee is unable to moderate the influence of financial distress and opinion shopping on the acceptance of going concern audit opinions.